2021
DOI: 10.3390/atmos12020231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the COVID-19 Lockdown Effects on Spectral Aerosol Scattering and Absorption Properties in Athens, Greece

Abstract: COVID-19 is evolving into one of the worst pandemics in recent history, claiming a death toll of over 1.5 million as of December 2020. In an attempt to limit the expansion of the pandemic in its initial phase, nearly all countries imposed restriction measures, which resulted in an unprecedented reduction of air pollution. This study aims to assess the impact of the lockdown effects due to COVID-19 on in situ measured aerosol properties, namely spectral-scattering (bsca) and absorption (babs) coefficients, blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 136 publications
(216 reference statements)
2
7
0
Order By: Relevance
“…The AAE during MCO is higher, on average, by about 0.04-0.05. This finding is in line with recent studies on the impact of Athens lockdown on carbonaceous particle concentrations [59]. Interestingly, the difference in AAE during MCO compared with before MCO is least on Sunday.…”
Section: Diurnal Variations Of Bc Concentrations and Aaesupporting
confidence: 92%
“…The AAE during MCO is higher, on average, by about 0.04-0.05. This finding is in line with recent studies on the impact of Athens lockdown on carbonaceous particle concentrations [59]. Interestingly, the difference in AAE during MCO compared with before MCO is least on Sunday.…”
Section: Diurnal Variations Of Bc Concentrations and Aaesupporting
confidence: 92%
“…The reduction in gas consumption and sharp reduction in international and domestic air traffic have also an important role in the reduction of the SO 2 levels around the world (Biswas et al 2020 ; Filonchyk and Peterson 2020 ; Pei et al 2021 ). Regarding O 3 , as a secondary pollutant, due to the NOx-sensitive regime, the observed reduction in NOx emissions would cause an increase in O 3 levels under a potential VOC-sensitive regime (Tables 3 – 4 and Figure 4 ) (Broomandi et al 2020 ; Casado-Aranda et al 2021 ; Kaskaoutis et al 2021 ; Kerimray et al 2020 ; Kumari and Toshniwal 2020 ; Lian et al 2020 ; Lokhandwala and Gautam 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lower levels of emissions, including the reduced concentrations of the light-absorbing OC and BC ( Ramanathan & Carmichael, 2008 ; Tiwari et al, 2016 ), might have significantly altered the radiative forcing and consequently changed the LSTs. Some studies have also demonstrated decreased aerosol radiative forcing values (–24.3 W m −2 at surface and –16 W m −2 at TOA in the short wave) due to lower AODs during the lockdown period in Madrid ( Barragan et al, 2020 ) and considerable decreases in carbonaceous aerosol (BC and Brown Carbon) absorption in Wuhan ( Wang et al, 2021 ) and Athens ( Kaskaoutis et al, 2021 ). In addition, a decrease in the radiative forcing in East Asia was attributed to reductions in AOD, with one‐third of the reduced anomalies to be attributed to the lockdown, while the remaining was attributed to natural factors, such as meteorological variability and surface heterogeneity ( Ming et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 lockdowns, satellite-derived AOD data revealed that the aerosol levels reduced substantially by 40–60% across urban areas in south and southeast Asia ( Kanniah et al, 2020 ; Pathakoti et al, 2021 ; Ranjan et al, 2020 ). Recent works also revealed a large reduction in BC levels, as well as significant modulations in aerosol scattering and absorption properties enabling to modify the radiation budget and temperature at the surface and in the lower atmosphere ( Anil & Alagha, 2020 ; Kaskaoutis et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%